(untitled) - Olga Shivairová; Sylva Bártlová; Věra Hellerová; Ivana Chloubová (University of Ostrava, 2023)
Aim: The aim of the research was to ascertain the feelings of frontline nurses during the Covid-19 pandemic. Design: Qualitative research using a phenomenological approach. Methods: Qualitative research using a phenomenological approach was carried out with eight nurses working with Covid-19 patients in a hospital and in a seniors home in Kladno, in the Central Bohemia region of the Czech Republic. Two diagrams, which show ties between identified categories, were generated based on results. Results: External stresses during the first wave were: lack of information, lack of protective equipment, different attitudes towards the pandemic management. During the third wave, they were: lack of nurses and other medical personnel, overwhelming of the healthcare system, too much administrative work, and long working hours spent in protective gear. The stress-reducing factors revealed after the first wave were: solidarity and gratitude expressed by society. During the third wave, nurses noted greater self-confidence and pride, better interpersonal relationships. Conclusion: The effective management of stressors in the pandemic period can contribute to better healthcare. Therefore, we should pay more attention to describe of them in future.